Modulated anodization synthesis of Sn-doped iron oxide with enhanced solar water splitting performance. (June 2019) - Lv, Xincong; Rodriguez, Ingrid; Hu, Chenyan; Shang, Jin; Sit, Patrick H.-L.; Ye, Changhui; Oskam, Gerko; Teoh, Wey Yang
Abstract: Modulated anodization synthesis is introduced here for the fabrication of porous Sn-doped iron oxide. Continuous square-wave modulation consisting of highly positive (+50 to +80 V range) and slightly negative potentials (−2 to −10 V range) at 100 Hz allowed the etching anodization of the metallic Fe foil and incorporation of Sn-dopant from the fluoride anion–containing electrolyte, respectively. Compared with the undoped iron oxide, the surface-enriched Sn-dopant (in the form of Sn 4+ ) alleviates the trapping and recombination of surface holes, while enhancing the hole transfer at the surface states. As such, the overpotential for photoelectrochemical (PEC) water oxidation was reduced by 110 mV and photocurrent density doubled. The incorporation of Co-Pi co-catalyst further improved the hole transfer efficiency, resulting in further reduction in overpotential by another 330 mV with respect to the bare Sn-doped iron oxide and significant improvement in photocurrent density at potentials below +1.23 V vs. reversible hydrogen electrode. Lastly, the iron oxide electrodes exhibit highly stable PEC water oxidation with no degradation in activity throughout the 10 h assessment under simulated solar irradiation and Faradaic efficiency of 90%. We envisage that the modulated anodization technique can be conveniently incorporated for a wide range of other dopants in search of efficient solar water splitting electrodes. Highlights: Modulated anodization synthesis of iron oxide with in situ Sn-doping is introduced. Sn-doped iron oxide shows highly photoelectrochemical water splitting efficiency. Onset potential was reduced by 330 mV when decorated with Co-Pi co-catalyst. Highly stable solar water splitting performance throughout 10 h assessment.